2012
DOI: 10.1002/ijc.27573
|View full text |Cite
|
Sign up to set email alerts
|

MDM2 SNP285 does not antagonize the effect of SNP309 in lung cancer

Abstract: Conflicting reports exist regarding the contribution of SNP309 in MDM2 to cancer risk. Recently, SNP285 was shown to act as an antagonist to SNP309 by over-riding the effect of SNP309 on SP1-mediated transcription. Moreover, SNP285 modified the relationship between SNP309 and risk of breast, ovarian and endometrial cancer. We assessed whether SNP285 confounded the effect of SNP309 in lung cancer in a cohort of 720 controls and 556 cases. Our cohort included both Caucasians and African Americans. Neither SNP309… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
28
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(33 citation statements)
references
References 25 publications
4
28
0
1
Order By: Relevance
“…In the study, the frequency of the MDM2 309G alleles among the controls was 0.544, which is almost identical to the frequency observed in the Japanese (0.525) (20), Han Chinese of southeast China (0.499) (14) and Korean (0.534) (16) populations; but is significantly higher compared to the Han Chinese of northeast China (0.455) (15), Caucasian (0.346-0.393) (11)(12)(13)18,38) and African-American (0.109-0.112) (13,38) populations (Fig. 1).…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…In the study, the frequency of the MDM2 309G alleles among the controls was 0.544, which is almost identical to the frequency observed in the Japanese (0.525) (20), Han Chinese of southeast China (0.499) (14) and Korean (0.534) (16) populations; but is significantly higher compared to the Han Chinese of northeast China (0.455) (15), Caucasian (0.346-0.393) (11)(12)(13)18,38) and African-American (0.109-0.112) (13,38) populations (Fig. 1).…”
Section: Discussionsupporting
confidence: 73%
“…As an example of population heterogeneity, an interaction of c.309T>G with c.285G>C in the MDM2 gene was questionable (43), as it has been previously reported to act as an antagonist by overriding the effect of c.309T>G on Sp1-mediated transcription. However, the study by Ryan et al (38) recently reported that c.285G>C did not antagonize the effect of c.309T>G in lung cancer. Furthermore, the differences in frequencies of driver mutations, such as EGFR mutations (44), may contribute to the different effects of c.309T>G in various ethnic groups.…”
Section: T/t (%) T/g (%) G/g (%) T/t Vs G/g T/t Vs T/g+g/g T/t+t/g mentioning
confidence: 93%
“…However, recently, some reports [17,20] concluded that the T allele was a poor prognosis factor in Asians. Furthermore, three reports found no association between SNP309 and lung cancer survival in Asian [18,19], Caucasian and African-American [12].…”
Section: Mdm2 Snp309 and Lung Cancer Prognosesmentioning
confidence: 98%
“…SNP285 has been reported to nullify the effect of SNP309 and to reduced risk of breast, endometrial, and ovarian cancer. Molecular epidemiological studies of the c.309T>G polymorphisms in terms of lung cancer susceptibility [11][12][13] have yielded contradictory findings. We recently reported that c.309T>G was not associated with lung cancer susceptibility in a Japanese population [14].…”
Section: Mdm2 Snp309 and Lung Cancer Prognosesmentioning
confidence: 99%
See 1 more Smart Citation